Experiences in seeking professional care for individuals with temporomandibular disorders: a qualitative study - Marçal, Jene Caroline Silva; Mendes, Luana Maria Ramos; Dietrich Deitos Rosa, Milena; Menezes, Luana Denadai Oliveira; Neves, Andrey Aparecido Dognani; Florêncio, Lidiane Lima; Palacios-Ceña, Domingo; Grossi, Debora Bevilaqua (Headache Medicine, 2024)
Introduction: Temporomandibular disorders (TMD) are a group of musculoskeletal and neuromuscular conditions that involve the temporomandibular joints, masticatory muscles and associated tissues. This condition affects approximately 10% of the population, and up to two-thirds seek professional care. However, it is common to encounter difficulties when looking for a specialist professional to obtain correct information and receive care promptly. Objective: To report the experiences of individuals with TMD in the health service and understand their perceptions regarding the search for specialized professional care. Methods: This is a qualitative, descriptive and exploratory study, following COREQ and SRQR, approved by the CEP (CAAE: 67213923.0.0000.5440), which interviewed 12 individuals aged between 18 and 40 years old, diagnosed with TMD according to DC/TMD. A semi-structured interview was carried out, recorded and transcribed. Thematic analysis and inductive modification were used. Results: The interview data established two themes: 1) Experiences related to the health service and 2) Motivations for searching for a professional. Patients were told that they had doubts about which professional they should look for to report their signs and symptoms related to TMD, as well as the difficulty in finding professionals specialized in treating the dysfunction and the high cost of accessing these professionals when found. Patients also say they expect good care and treatment to resolve their problems. Professional conduct is also based on dialogue, guidance and explanation about the dysfunction and the partnership between professional and patient to create a better treatment plan. Conclusion: The reports show the difficulty of finding a specialized professional to deal with complaints related to TMD and how much this dysfunction requires greater visibility regarding which professionals the patient should seek to investigate their signs and symptoms. Furthermore, patients described the importance of having care focused on dialogue and attention to the complaints raised, designing a treatment plan together considering their observations and preferences.